The Curious Case of CTE: Mediating Materialities of Traumatic Brain Injury. (April 2019) - Ventresca, Matt
This article investigates how media discourses are sites for multiple "becomings" of chronic traumatic encephalopathy (CTE), a neurobiological condition associated with repetitive brain trauma. I explain that these discourses are contexts in which multiple actors (journalists, scientists, athletes, and sports organizations) struggle to represent the material complexities of CTE through competing ways of knowing. My analysis reveals two tensions underlying debates about sport-related traumatic brain injury. First, my examination reveals discursive clashes between emotionally charged representations of CTE as an urgent public health problem and commentary cautioning audiences about the scientific uncertainty surrounding CTE. I illuminate how, in the face of this uncertainty, scientific conclusiveness remains privileged as the basis for meaningful action to improve athletes' health. Second, inconsistencies across representations I examined illustrate how CTE defies a straightforward material-semiotic divide. These contradictions demonstrate how the materialities of CTE exceed the medico-scientific and lay discourses through which the condition is commonly known. I argue that such limitations should not enable stakeholders to overlook calls for drastic changes to how sports are played or deflect questions about how sports violence impacts athletes' lives. Instead, this level of uncertainty should accelerate (rather than delay) challenges to socially acceptable levels of sports violence.